Biosynthesis of very long chain polyunsaturated fatty acids in the leafy vegetable chicory - Mekky, Hattem; Mohamed, Maged; Lazarus, Colin; Power, J. Brian; Davey, Michael R (MTT Agrifood Research Finland, 2011)
The synthesis of very long chain polyunsaturated fatty acids (VLCPUFAs) was investigated in five cultivars of chicory. Genes for enzymes of the ù3/6 Ä8-desaturation biosynthetic pathways for the formation of C20 VLCPUFAs were inserted into chicory by Agrobacterium-mediated transformation of leaf explants. Plants were transformed by genes encoding Ä9-specific elongating activity from Isochrysis galbana, Ä8-desaturase from Euglena gracilis and Ä5-desaturase from Mortierella alpina, either separately or in combination; transgenic plants were selected on culture medium containing glufosinate ammonium for those transformed with the Ä9-elongase gene alone or in combination with the Ä8-desaturase gene, or kanamycin for plants transformed with the Ä5-desaturase gene. PCR showed the presence of the transgenes within the genome of selected plants, with RT-PCR confirming gene expression. Gas Chromatography of fatty acid methyl esters extracted from freeze-dried leaves of transgenic plants quantified the synthesis of omega-6 arachidonic acid and its precursors eicosadienoic and dihomo-ã-linolenic acids, and omega-3 eicosapentaenoic acid together with its precursors eicosatrienoic and eicosatetraenoic acids. This is the first report of the production of VLCPUFAs in a leafy vegetable. Since VLCPUFAs are the precursors of prostaglandins, the formation of prostaglandins was also investigated in chicory following a second transformation event using the PGHS-1 gene from Mus musculus.
Keywords: Ka; Very long chain polyunsaturated fatty acids (VLCPUFAs); Agrobacterium-mediated transformation; Ä8-desaturation biosynthetic pathways; transgenic plants; Gas Chromatography (GC)